(untitled) (Fiep Bulletin - online, 2016)
Introduction: A small net is one of the easiest and affordable to be used inside incubators PN resources , it brings many physiological benefits for the neurodevelopment of preterm infants that causes the patient to experience a closer approach of the comfort of the womb . Objective: To conduct a systematic review of literature on the topic prospost. Methods : Systematic review in Databases : Lilacs , Medline , PubMed , SciELO and Peter , with the following key words and its synonym and English : Positioning " positioning " Physiotherapy " Physiotherapy " , Hammock Method " HammockMethod " and Redinha led themselves in consideration for this research articles published between 1980 and 2014. Results: of the six articles included only two were high quality , with cardiorespiratory, hemodynamic and other outcomes . Conclusion: The results are heterogeneous and suggest new studies with better methodological designs.